University education in the age of the Internet : an urgent necessity and intractable challenges. - LOUAR, Warda (Journal of Human Sciences, 2020)
Informatics represents one of the most important aspects of our contemporary life, as its technologies became the basic elements of the environment, which led to its use in various activities, including education.  It has the ability to develop programs, and as a natural consequence, the use of the Internet in education has become the obvious and expected extension in all its stages, especially university education, this network has the ability of access for students and professors to exchange opinions and ideas, even without the presence of the professor, Then the information explosion poses a real challenge to the traditional methods of learning and education, and therefore educational renovation is no longer a luxury, but rather an urgent necessity required by actual era and its variables. Thus many studies and research have confirmed the degree of benefiting from the use of the Internet in the educational process and enriching scientific research in terms of positive effects such as the quality of educational outcomes, the skills, the experience and the  knowledge in a more effective way that enable both the teacher and student to face the challenges and keep pace with this accelerating technology era. So what position has the university professor in the rapid and sequential change; in terms of technology application, in both sides quantity and quality? What are the challenges faced by the university professor nowadays in the use of technology?